Relation between Sex Hormones and COVID 19 - Ihsan Raisan Ibrahim, Talib Rahiem Hussain (Pakistan Journal of Medical & Health Sciences, 2022)
Coronavirus is one of the major viruses that mainly attack human respiratory system . there are similarities in symptoms between COVID – 19 and earlier Coronavirus infections such as fever , dry cough , however , COVID – 19 showed unique clinical feature , that involve the targeting of the lower airways as evident by upper respiratory tract symptoms such as rhinorrhea , sneezing and sore throat . The severity of COVID- 19 as indicated by hospitalization , admission to intensive care unit , has been greater in men than women . Many hypotheses have been found to explain this difference in susceptibility and severity of the disease . The difference in immune response between sex is consider the main factor in outcomes of viral infection . Estrogen has immunoenhancing effect on the immune system , while testosterone has immunosuppressive role , also progesterone inhibits inflammatory innate immune response . In this review , its concluded that sex hormones have relation with COVID-19 severity .It was concluded that estrogen and progesterone reduce disease severity in contrast , testosterone increase the severity and susceptibility for COVID-19 .